(untitled) (Journal of Advances and Scholarly Researches in Allied Education, 2019)
The hybridities narrated in the texts of Gupta represents examples of interculturality personified. Once such mélange –save taken into account, self – fashioning becomes relatively easy and hybrid existence less painful. Defining selves in dislocated existence is an ever changing process. The process leads from one’s initial definition of self to an adopted definition of hybridity. Only by going through the pain of living in hybridity can one hope to reconcile with one’s dislocation and arrive at a new definition of self. This condition of increasing hybridity of the Indian diaspora is brought about by individual self – fashioning and the relationships between the protagonists of the texts discussed are part of this phenomenon.